Pengaruh Produk, Promosi, Dan Kualitas Terhadap Keputusan Untuk Menjadi Nasabah Bank Syariah Indonesia KC Kuala Simpang - Faisal Umardani Hasibuan (STIKes Ibnu Sina Ajibarang, 2023)
The purpose of this study was to determine the effect of product, promotion and service quality on the decision to become a customer at Bank Syariah Indonesia KC Kuala Simpang. The type of research used in this study is quantitative. The data collection technique used is a questionnaire. The population in this study were all customers at Bank Syariah Indonesia (BSI) KC Kuala Simpang, which at the end of 2019 totaled 1242 customers, while the sample in this study totaled 93 people. Data analysis techniques using the classical assumption test, multiple linear regression test, hypothesis testing and coefficient of determination test. The results of the study show that the product influences the decision to become a customer at Bank Syariah Indonesia KC Kuala Simpang. This is evidenced by the sig value of the product variable, namely 0.006 <0.05 (significance level) and the t-count value of 3.932 > 1.9869 (t-table). Promotion influences the decision to become a customer at Bank Syariah Indonesia KC Kuala Simpang. This is evidenced by the sig value of the promotion variable, which is 0.019 <0.05 (significance level) and the t-count value is 2.531 > 1.9869 (t-table). Service quality influences the decision to become a customer at Bank Syariah Indonesia KC Kuala Simpang. This is evidenced by the sig value of the service quality variable, which is 0.025 <0.05 (significance level) and the t-count value is 2.145 > 1.9869 (t-table). Products, promotions and service quality simultaneously influence the decision to become a customer at Bank Syariah Indonesia KC Kuala Simpang. This is proven based on the results of the F test obtained a sig value of 0.000 <0.05 (significant level α) and F count of 7.814 and it is known that df1 = k-1 = 4-1 = 3 and df2 = N-k = 93-4 = 89 ( F table = 2.71). So that F count > F table (7.814 > 2.71).